Medicinal Perspective of 2,4‐Thiazolidinediones Derivatives: An Insight into Recent Advancements - Gupta, Sneha; Jha, Sumeet; Rani, Supriya; Arora, Pinky; Kumar, Shubham (ChemistryOpen (Weinheim), 2024)
2,4‐Thiazolidinedione derivatives represent nitrogen‐containing heterocyclic compounds utilized in type 2 diabetes mellitus management. Recent advances in medicinal chemistry have unveiled diverse therapeutic potentials and structural modifications of these derivatives. This review delves into novel TZD derivatives, encompassing their synthesis, structure‐activity relationships, and pharmacokinetic profiles. Various therapeutic potentials of TZDs are explored, including anticancer, antimicrobial, anti‐inflammatory, antioxidant, anticonvulsant, antihyperlipidemic, anticorrosive, and antitubercular activities. Additionally, it addresses mitigating side effects associated with marketed TZD derivatives such as weight gain, oedema, fractures, and congestive heart failure in type 2 diabetes mellitus management. The review elaborates on in vivo, in vitro, and ex vivo studies supporting different biological activities, alongside predicting ADME and drug‐likeness properties of TZDs. Computational studies are also integrated to elucidate binding modes and affinities of novel TZD derivatives. Furthermore, a plethora of novel TZD derivatives with varied and enhanced therapeutic potentials are presented, warranting further evaluation of their biological activities. This article reviews recent advancements in the medicinal chemistry of 2,4‐thiazolidinedione derivatives, focusing on their synthesis, characterization, and therapeutic potential. Emphasis is placed on their roles in treating various diseases, highlighting their significance in medicinal chemistry and future perspectives.